Practical problems in cold storage - Holloway, A. Dexter (My University, 1907)
Introduction: In a study of cold storage one finds an endless task as one subject is taken up and studied it leads to other problems. Madison Cooper, an eminent authority on cold storage, says that there are four chief uses of cold storage and from his book on practical cold storage these uses are taken. 1. To prevent premature decay of perishable products. 2. To lengthen the period of consumption and thus greatly increase production. 3. To enable the owner to market his products at will. 4. To make possible transportation, in good condition, from point of production to point of consumption, inspective of distance. Cold storage makes it possible to…
Citation: Holloway, A. Dexter. Practical problems in cold storage. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Cold Storage; Refrigeration; Food Preservation; Theses; Manuscripts (documents)